Evaluation of the Implementation of the Merdeka Curriculum at State High School 13 (Driver School) in Ambon City - Manuputty, Rina Asrini; Rahabav, Patrisius; Sahalessy, Arnold (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2024)
The Merdeka Belajar policy is implemented to accelerate the achievement of national education goals, namely increasing the quality of Indonesia's human resources which have superiority and competitiveness compared to other countries. The quality of superior and competitive human resources is realized in students who have noble character and have a high level of reasoning, especially in literacy and numeracy. However, in reality there are still many teachers who experience obstacles in implementing the implications of the independent curriculum, especially in choosing learning media that suit the demands of the independent curriculum. The aim of this research is to look at planning, implementation, evaluation, as well as inhibiting and supporting factors in implementing the independent curriculum in driving schools. The research method used is the CIPP model (Context, Input, Process, Product). The results of the research show that the Evaluation of the Implementation of the Merdeka Curriculum at SMA Negeri 13 Ambon shows good results in implementing the Merdeka Curriculum at SMA Negeri 13 Ambon, so that the Literacy, Numeracy and P-5 learning outcomes support the production of quality and competitiveness of graduates in universities and Academic Achievement